Writing self, writing empire : Chandar Bhan Brahman and the cultural world of the Indo-Persian state secretary - Kinra, Rajeev (South Asia across the disciplines., 2015)
"Writing Self, Writing Empire examines the life, career, and writings of the Mughal state secretary, or Munshi, Chandar Bhan 'Brahman' (d. c.1670), one of the great Indo-Persian poets and prose stylists of early modern South Asia. Chandar Bhan's life spanned the reigns of four different emperors, Akbar (1556-1605), Jahangir (1605-1627), Shah Jahan (1628-1658), and Aurangzeb 'Alamgir (1658-1707), the last of the 'Great Mughals' whose courts dominated the culture and politics of the subcontinent at the height of the empire's power, territorial reach, and global influence"--Provided by publisher.